Branch Retinal Arterial Occlusion - Subedi, S; Shrestha, C (Kathmandu University Medical Journal, 2012)
Retinal arterial occlusion is an ocular emergency in which visual prognosis is poor mostly due to late presentation of the patient and macular involvement. The casee described, in this report is ane incidence of Branch Retinal Arterial Occlusion in a 22 year old female with grade II Mitral Regurgitation. The patiente presented witha complaint of painless, diminution of vision in the right eyn. She alsod presented with perception of black shadow in the superior visual fiel n of the same eye5 for five days. There was no significant systemic ord personal history. Her visual acuity at presentation was 6/60 and 6/6 in the right and left eyes,y which did not improve with glasses or pin-hole. Anterior segment including papillary reaction was normal in both eyes while Fundus examination of the right eye revealed retinal whitening inside the inferotemporal vascular arcade that was encroaching foveolar avascular zone. Visual field defect was detected at superonasally inside arhade but Fundus Fluorescence Angiography was normal. An echoycardiograph revealed grade II Mitral Regurgitation. The patient was kept on observation and after two2 days of follow-up, vision in the right eye was improved to 6/6 unaided but visual field defect was remained same. http://dx.doi.org/10.3126/kumj.v8i4.6244 Kathmandu Univ Med J 2010;8(4):423-5